Do Dentistry and physical education students know the importance of mouthguard usage in sports practice? - Priscilla Maria Lima do NASCIMENTO; Danielle Ferreira SOBRAL-SOUZA; Paulo Cardoso LINS FILHO; Rafael Antonio de Oliveira RIBEIRO; Hilcia Mezzalira TEIXEIRA; Alexandre Batista do NASCIMENTO (Faculdade São Leopoldo Mandic, 2019)
Objective: The purpose of the present study was to evaluate the knowledge of Dentistry and Physical Education students on mouthguard usage in sports practice. Methods: A form containing questions that demonstrated participants' knowledge about the use of mouthguards was applied. Inclusion criteria were: individuals older than 18 years who were attending Dentistry or Physical Education courses from the sixth period and who agreed to participate in the study, and the exclusion criteria for dentistry students were: attended the discipline of Dental Materials II of UFPE and already participated in internships in schools or academies for the participants of the Physical Education course. Results: it was possible to observe that 97% of the interviewees know what a mouthguard is, but none of the participants would be able to indicate a specific type of mouthguard to sportsmen. Conclusion: It was possible to conclude that a large number of the interviewees know what a mouthguard is, but not enough to indicate which is the safest protector.